PENGARUH UKURAN PERUSAHAAN DAN PROFITABILITAS, TERHADAP KOEFISIEN RESPON LABA PADA MASA PANDEMI (Study Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di BEI 2020). - Shinta Lutmila Safitri; Anik Malikah; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2021)
The purpose of this study was to determine the effect of firm size and profitability on the profit response coefficient in the pandemic period. The empirical study in this study is a manufacturing company listed on the Indonesia Stock Exchange in 2020. The population in this study are all manufacturing companies listed on the IDX. The sampling technique used purposive sampling and obtained as many as 59 companies that meet the specified criteria. The data analysis method used in this research is multiple linear regression analysis. The results of this study show that simultaneously the variables of firm size and profitability have a significant positive effect on the earnings response coefficient during the pandemic. Partially, the size of the company affects the earnings response coefficient during the pandemic. The profitability variable partially affects the profit response coefficient during the pandemic.Keywords: company size, profitability, profit response